Total and High Molecular Weight Adiponectin Expression Is Decreased in Patients with Common Variable Immunodeficiency: Correlation with Ig Replacement Therapy - Pecoraro, Antonio; Nigro, Ersilia; Polito, Rita; Monaco, Maria Ludovica; Scudiero, Olga; Mormile, Ilaria; Cesoni Marcelli, Azzurra; Capasso, Mario; Habetswallner, Francesco; Genovese, Arturo; Daniele, Aurora; Spadaro, Giuseppe (Frontiers in Immunology, 2017)
Adiponectin (Acrp30) is an adipokine widely studied for its beneficial metabolic properties. It circulates as low molecular weight (LMW), medium molecular weight (MMW) and high molecular weight (HMW) oligomers. The latter exert the most potent biological effects. Acrp30 attracted renewed interest with the finding that it was associated with the development and progression of immune disorders. The mechanisms underlying this association and the role of Acrp30 in the pathophysiology of immune-mediated conditions remain unknown. Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by chronic activation of the immune system, impaired antibody production and imbalanced cytokine production. In the attempt to shed light on the expression of Acrp30 in CVID we: a) investigated total Acrp30 and its oligomerization state in CVID patients undergoing maintenance Ig replacement therapy; b) assessed the effects of Ig replacement therapy on Acrp30 expression in treatment-naïve CVID patients, namely, patients not treated before diagnosis, before and after the first Ig administration; and c) evaluated the correlation between Acrp30 levels and clinical phenotypes of the disease. As controls, we analyzed healthy subjects and patients affected by a non-immunodeficiency chronic inflammatory demyelinating polyneuropathy (CIDP), before and after Ig infusion. We found that total Acrp30 and HMW oligomers were decreased in CVID but not in CIDP patients versus controls. Moreover, Acrp30 levels were correlated with IgA levels and were associated with two CVID phenotypes, namely, autoimmune cytopenia and enteropathy. Receiver operating characteristic curve analysis indicated that Acrp30 modulation is specific for CVID patients. Acrp30 and HMW levels quickly and dramatically increased after Ig infusion only in eight treatment-naïve CVID patients but not in five CIDP patients. This finding indicates that Ig administration per se is not able to induce an increase of Acrp30, but the specific cellular and/or molecular background proper of CVID seems to be essential. In conclusion, our data indicate that Acrp30 is specifically related to CVID activity. Further studies are required to understand the biological role of Acrp30 and its possible use as disease biomarker in CVID.